Fidelity-Aware Replication for Mobile Devices - Ramasubramanian, Venugopalan; Veeraraghavan, Kaushik; PUttaswamy, Krishna P. N.; Rodeheffer, Tom; Terry, Doug; Wobber, Ted (IEEE Transactions on Mobile Computing, 2010)
Mobile devices often store data in reduced resolutions or custom formats in order to accommodate resource constraints and tailor-made software. The Polyjuz framework enables sharing and synchronization of data across a collection of personal devices that use formats of different fidelity. Layered transparently between the application and an off-the-shelf replication platform, Polyjuz bridges the isolated worlds of different data formats. With Polyjuz, data items created or updated on high-fidelity devices—such as laptops and desktops—are automatically replicated onto low-fidelity, mobile devices. Similarly, data items updated on low-fidelity devices are reintegrated with their high-fidelity counterparts when possible. Polyjuz performs these fidelity reductions and reintegrations as devices exchange data in a peer-to-peer manner, ultimately extending the eventual-consistency guarantee of the underlying replication platform to the multifidelity universe. In this paper, we present the design and implementation of Polyjuz and demonstrate its benefits for fidelity-aware contacts management and picture sharing applications.